Scaling smartness, (de)provincialising the city? The ASEAN Smart Cities Network and the translational politics of technocratic regionalism - KONG, Lily (Institutional Knowledge at Singapore Management University, 2021)
This paper explores the case study of the ASEAN Smart Cities Network (ASCN) to uncover the motivations and potential challenges associated with technocratic regionalism, by which we mean technology-driven forms of regional integration and consolidation. In the case of the ASCN, technocratic regionalism is used to spur urban development through the rollout of smart city plans, policies and projects across Southeast Asia. As such, it is a regional strategy designed to scale smartness, and thus deprovincialise the city by embedding it within transnational flows of capital, ideas and expertise. At the same time, however, already existing urban issues have the potential to re-provincialise the city. The vagaries of local contexts, structures of governance and urban cultures complicate processes of scalar ascendency and thus foreground the paradox of (de)provincialisation. We identify three challenges – divergent infrastructural developments, vertical and horizontal (non-)integration, and the need to reconcile (in)formal spaces of the “smart” city – that underpin the translational politics of technocratic regionalism, and which are likely to compromise the efficacy and success of the ASCN.